Dysphagia presentation and management following coronavirus disease 2019: an acute care tertiary centre experience. Issue 11 (10th November 2020) - Dawson, C; Capewell, R; Ellis, S; Matthews, S; Adamson, S; Wood, M; Fitch, L; Reid, K; Shaw, M; Wheeler, J; Pracy, P; Nankivell, P; et al.
Abstract: Objectives: As the pathophysiology of Covid-19 emerges, this paper describes dysphagia as a sequela of the disease, including its diagnosis and management, hypothesised causes, symptomatology in relation to viral progression, and concurrent variables such as intubation, tracheostomy and delirium, at a tertiary UK hospital. Results: During the first wave of the Covid-19 pandemic, 208 out of 736 patients (28.9 per cent) admitted to our institution with SARS-CoV-2 were referred for swallow assessment. Of the 208 patients, 102 were admitted to the intensive treatment unit for mechanical ventilation support, of which 82 were tracheostomised. The majority of patients regained near normal swallow function prior to discharge, regardless of intubation duration or tracheostomy status. Conclusion: Dysphagia is prevalent in patients admitted either to the intensive treatment unit or the ward with Covid-19 related respiratory issues. This paper describes the crucial role of intensive swallow rehabilitation to manage dysphagia associated with this disease, including therapeutic respiratory weaning for those with a tracheostomy.